The Implementation of Video Digital Storytelling to Increase Students Speaking Ability - Vina Evelyn Aulia Panggabean; Juliana Juliana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2023)
This research examines the implementation of video digital storytelling as an innovative media to enhance students' speaking ability. Video digital storytelling involves the creation of short, multimedia narratives that integrate images, videos, and audio to convey personal or fictional stories. The research aimed to encourage students to actively engage in spoken communication, express themselves creatively, and develop their oral language skills. The study investigates 25 students who participated using video digital storytelling in learning English as a means to increase their speaking ability in English as a Second Language (ESL) context. The research design was based on a case study with a thematic questionnaire was used for data collection. The results of students' post-test scores show an increase in students' speaking ability. The average post test score of students’ speaking ability was 79.4. From the findings of the questionnaire indicated positive outcomes in terms of active engagement, motivation, collaboration, communication, confidence building, critical thinking, application of knowledge, and satisfaction through the usage of video digital storytelling for students in speaking ability. In short, the students enjoyed learning and participating in various speaking assignments by using video digital storytelling.